Changes in site-specific shape resonances in nitrogen K-shell photoionization of N2O induced by vibrational excitation. (5th March 2018) - Hoshino, M; Kato, H; Kuze, N; Tanaka, H; Fukuzawa, H; Ueda, K; Lucchese, R R
Abstract: The central (Nc ) and terminal (Nt ) nitrogen K-shell photoelectron spectra (PESs) of N2 O molecules have been measured in the σ shape resonance energy region at temperatures of ∼300 and ∼630 K. Estimating vibrational populations based on the Boltzmann distribution at these temperatures, PESs of vibrationally ground and bending-excited levels in the initial electronic ground state were extracted. Vibrationally integrated partial cross sections and asymmetry parameters for ionization from vibrationally ground and bending-excited levels were obtained as a function of the incident photon energy by integrating PESs over the vibrational levels of the core-hole states. In Nc photoionization, the shape resonance from the bending-excited level was found to be shifted to the lower photon energy side and to become narrower than that from the ground vibrational level. In Nt photoionization from the bending-excited level, the downward shift of the resonance is more significant than that in Nc ionization. These experimental findings are qualitatively consistent with theoretical predictions and suggest that the shape resonance associated with the Nt core hole is more sensitive to the bending angle of the initial state than is the shape resonance associated with the Nc core hole. The asymmetry parameters for photoionization from the bending-excited level, however, showed almost the same behavior as those from the ground vibrational level for both K-shell photoionization channels and in the photon energy range studied here.